Granulocyte antibodies in male blood donors: can they trigger transfusion‐related acute lung injury?. Issue 8 (29th April 2018) - Nguyen, Xuan‐Duc; Schulze, Torsten J.; Bugert, Peter; Lauber‐Härtl, Stephanie; Schulz‐Linkholt, Monika; González‐Schulze, Karen; Reil, Angelika; Dengler, Thomas; Panzer, Simon; Seifried, Erhard
Abstract : BACKGROUND: White blood cell–associated antibodies can lead to transfusion‐related acute lung injury (TRALI). Female donors with a history of pregnancies have been identified as a main cause for these antibodies. Male or female donors without a history of pregnancy are considered as safe donors. STUDY DESIGN AND METHODS: Following the identification of two TRALI cases associated with blood products from male donors, we investigated the frequency of granulocyte‐specific and human leukocyte antigen (HLA) antibodies in the entire blood donor population using a high throughput automated flow‐cytometry–based granulocyte immunofluorescence test (Flow‐GIFT). We investigated sera from 14, 343 whole blood donors (female, n = 6974, 48.7%; male, n = 7369, 51.3%) using automated Flow‐GIFT. Of the female blood donors, 60.4% had a history of pregnancy. Positive sera were retested by the standard granulocyte immunofluorescence test and granulocyte agglutination test. For the detection of HLA Class I and II immunoglobulin G antibodies, we used a commercial screening enzyme‐linked immunosorbent assay. RESULTS: We detected in 924 (21.9%) of the 4212 females with a history of pregnancy antibodies against granulocyte antigens (n = 62, 1.5%), HLA Class I and/or II antigens (n = 864, 20.5%). Notably, in 3.5% (n = 96) of 2762 females without a history of pregnancy and in 2.1% (n = 154) of 7369 males antibodies against granulocyte antigens (n = 13, 0.47% and n = 45, 0.6%), HLA Class I and/or II (n = 83, 3% and n = 109, 1.4%, respectively), were also detected. CONCLUSION: Human neutrophil antigen antibodies are rare in male and females without a history of pregnancy compared to females with a history of pregnancy, but their relevance is not negligible.